Characterization of the translocon of the outer envelope of chloroplasts - Schleiff, Enrico (The Rockefeller University Press, 2003)
The protein translocon of the outer envelope of chloroplasts (Toc) consists of the core subunits Toc159, Toc75, and Toc34. To investigate the molecular structure, the core complex was purified. This core complex has an apparent molecular mass of ∼500 kD and a molecular stoichiometry of 1:4:4–5 between Toc159, Toc75, and Toc34. The isolated translocon recognizes both transit sequences and precursor proteins in a GTP-dependent manner, suggesting its functional integrity. The complex is embedded by the lipids phosphatidylcholine and digalactosyldiacylglyceride. Two-dimensional structural analysis by EM revealed roughly circular particles consistent with the formation of a stable core complex. The particles show a diameter of ∼130 Å with a solid ring and a less dense interior structure. A three-dimensional map obtained by random conical tilt reconstruction of electron micrographs suggests that a “finger”-like central region separates four curved translocation channels within one complex.